A study of program efficiency in Institute Of Islamic Understanding Malaysia (IKIM) / Muhamad Shahidan Hassan - Hassan, Muhamad Shahidan (2019)
Today, various Islamic institutions have existed in Malaysia. These institutions act as a "think tank" and implemented in every matter related to Islamic in administration in Malaysia. Thus, these institutions have undertaken various efforts to achieve their objectives. Like manage the programs, seminars, muzakarah and so on. Since, various problems have occurred among Muslims. So, it has raised the question of how effective the program that implemented?. Accordingly, the data are taken from the programs conducted by IKIM.